2011
DOI: 10.1002/jnr.22795
|View full text |Cite
|
Sign up to set email alerts
|

Expression of sorting nexin 12 is regulated in developing cerebral cortical neurons

Abstract: The sorting nexins (SNXs) are a family of proteins functioning in diverse processes, including endocytosis, endosomal sorting, and endosomal signaling. Sorting nexin 12 (SNX12) is one of the SNXs family members; however, its function remains unknown. To clarify the function of SNX12, in this study, we first investigated the expression profiles in mice, particularly in the central nervous system (CNS), and then analyzed the functional role on neurite outgrowth. We found that SNX12 was widely expressed in the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Recently one study reported that SNX12 is widely expressed in the adult mouse central nervous system and thus suggested that SNX12 might regulate neurite formation during cerebral cortical development [26]. Herein, we found that SNX12 is abundantly expressed in mouse cerebrum and cerebellum in addition to other tissues (Figure 2A).…”
Section: Resultsmentioning
confidence: 50%
“…Recently one study reported that SNX12 is widely expressed in the adult mouse central nervous system and thus suggested that SNX12 might regulate neurite formation during cerebral cortical development [26]. Herein, we found that SNX12 is abundantly expressed in mouse cerebrum and cerebellum in addition to other tissues (Figure 2A).…”
Section: Resultsmentioning
confidence: 50%
“…Cerebral cortical neurons were isolated from E18.5 Sprague-Dawley (SD) rat fetuses [28]. The brains were removed, and the neocortices were dissected out.…”
Section: Methodsmentioning
confidence: 99%
“…1C). Although SNX12 is widely expressed in brain (Mizutani et al, 2012;Zhao et al, 2012), it is Fig. 1.…”
Section: Introductionmentioning
confidence: 99%